2022
DOI: 10.1007/s11136-022-03261-5
|View full text |Cite
|
Sign up to set email alerts
|

Are OMERACT recommendations followed in clinical trials on fibromyalgia? A systematic review of patient-reported outcomes and their measures

Abstract: Purpose Patient-Reported Outcomes (PROs) and its measures (PROMs) are key to outcome assessment in Fibromyalgia (FM) trials. The aim of this review was to investigate which domains and instruments were assessed in recent FM trials and to compare them to recommendations by the Outcome Measures in Rheumatology (OMERACT) initiative. In addition, we investigated the overlap with a generic health assessment approach, i.e. eight domains suggested by the Patient-Reported Outcome Measurement Information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…Many different scoring systems are currently in use including average pain daily score (ADPS), weekly average worst daily pain score (W-DPS), Brief Pain Inventory and Fibromyalgia Impact Questionnaire (FIQ) [ 27 ]. However, to date there is no consensus on patient reported outcome measures (PROMs) used in fibromyalgia research [ 28 ]. This makes comparison between different therapeutic agents challenging [ [29] , [30] , [31] ].…”
Section: Discussionmentioning
confidence: 99%
“…Many different scoring systems are currently in use including average pain daily score (ADPS), weekly average worst daily pain score (W-DPS), Brief Pain Inventory and Fibromyalgia Impact Questionnaire (FIQ) [ 27 ]. However, to date there is no consensus on patient reported outcome measures (PROMs) used in fibromyalgia research [ 28 ]. This makes comparison between different therapeutic agents challenging [ [29] , [30] , [31] ].…”
Section: Discussionmentioning
confidence: 99%
“…11 A systematic review published in 2023 found that 81.9% of 107 FM trials applied both versions of the FIQ as outcomes measures. 12 The revised version is strongly associated with the original FIQ and has excellent psychometric properties (Cronbach α = 0.95) and good convergent and discriminant validity, 13 and it distinguishes FM patients from patients with rheumatoid arthritis, systemic lupus erythematosus, and major depressive disorders. 13 The FIQR encompasses 3 domains: physical functioning, overall impact, and symptoms.…”
Section: Introductionmentioning
confidence: 99%